2011
DOI: 10.1007/s10741-011-9266-y
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases (TIMPs) in heart failure

Abstract: Remodeling of the myocardium and the extracellular matrix (ECM) occurs in heart failure irrespective of its initial cause. The ECM serves as a scaffold to provide structural support as well as housing a number of cytokines and growth factors. Hence, disruption of the ECM will result in structural instability as well as activation of a number of signaling pathways that could lead to fibrosis, hypertrophy, and apoptosis. The ECM is a dynamic entity that undergoes constant turnover, and the integrity of its netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 143 publications
(120 reference statements)
4
106
0
3
Order By: Relevance
“…Enhanced MMP2 Activation in Timp3 Ϫ/Ϫ Mice following 2 Weeks of Angiotensin II Infusion-TIMP3 is a potent inhibitor of a number of active MMPs and can inhibit cell surface activation of MMP2 (33); hence, its absence can lead to uncontrolled proteolytic activities (34). In situ gelatin zymography showed that Ang II infusion resulted in a stronger gelatinase activity in Timp3 Ϫ/Ϫ compared with WT aorta ( Fig.…”
Section: Timp3-deficient Mice Exhibit Adverse Aorticmentioning
confidence: 99%
“…Enhanced MMP2 Activation in Timp3 Ϫ/Ϫ Mice following 2 Weeks of Angiotensin II Infusion-TIMP3 is a potent inhibitor of a number of active MMPs and can inhibit cell surface activation of MMP2 (33); hence, its absence can lead to uncontrolled proteolytic activities (34). In situ gelatin zymography showed that Ang II infusion resulted in a stronger gelatinase activity in Timp3 Ϫ/Ϫ compared with WT aorta ( Fig.…”
Section: Timp3-deficient Mice Exhibit Adverse Aorticmentioning
confidence: 99%
“…CFBs also produce matrix metalloproteinases (MMPs) as well as tissue inhibitors of MMPs (TIMPs), which are ECM-regulatory proteins. MMPs are proteases that degrade ECM proteins and TIMPs can inhibit MMP function; their balanced equilibrium is critical for ECM homeostasis (59). Fibrosis is a response of hyperactivity of CFBs that proliferates in response to certain stressful stimuli, and recruitment and proliferation of circulating bone marrow-derived cells that infiltrate the myocardium and transform into CFBs (60).…”
Section: Cardiac Injury Leads To Fibrosismentioning
confidence: 99%
“…Function of MMPs is balanced by their inhibitors, tissue inhibitor of metalloproteinase (TIMPs) to achieve optimal ECM composition [24]. Impairment of this delicate balance is fundamental to the pathogenesis of aortic aneurysm formation, expansion and rupture [5,15,[25][26][27][28].…”
Section: Matrix Metalloproteases and Their Inhibitors In Aaamentioning
confidence: 99%
“…AAA = abdominal aortic aneurysm; ApoE = apolipoprotein E; CaCl 2 =calcium chloride; MCP-4 = mast cell protein-4; MMP = matrix metalloproteinase; plg = plasminogen; TAA = thoracic aortic aneurysm; TIMP = tissue inhibitor of matrix metalloproteinase. ranging from 21-30 kDa that serve as potent endogenous inhibitors of MMPs through a covalent bond between their N-terminus and the catalytic domain in the activated MMPs [24]. All four TIMPs (TIMP1-4) are found in vertebrates and their expression levels are modulated during tissue remodelling or development [29].…”
Section: Matrix Metalloproteases and Their Inhibitors In Aaamentioning
confidence: 99%
See 1 more Smart Citation